Structural controls on polyphase hydrothermal dolomitization in the Kinta Valley, Malaysia: Paragenesis and regional tectono-magmatism - Ramkumar, M. (2019)
In the eastern side of the Malay Peninsula, thick successions of limestone formations preserve important records of the Mesozoic and Cenozoic tectonic events. Here we investigate the strata- and fracture-bound hydrothermal dolomites in the Palaeozoic carbonates of the Kinta Valley, western Peninsular Malaysia. Based on their textural and morphologic characteristics, structural relationships with the host rock, different facies types, and associations with hydrothermal calcite and low-grade metamorphic marble, we attempt to trace their polyphase origin and relationship with thermo-tectonic events of the region. A detailed evaluation of the nature of brecciation and crystallization of polyphase dolomites, dolomitic limestones, limestones and marble, under the influences of episodic faulting, is associated with the regional structural geology with emphasis on pre-existing fault reactivations, granitic emplacement and progressive thermal influence. Supply of Mg 2+ from the host rock for dolomitization, limited and episodic influx of circulating fluids and cessation of thermo-tectonic evolution with progressive cooling are also inferred. Correlating the geological events in western Peninsular Malaysia with regional structural dynamics reveals that the major deformation episodes exerted first order controls on the loci of dolomite occurrences. The occurrence, geometry and structural relationships of the dolomites were controlled by successive magmatic events, whereas, the intensity of replacement dolomitization was controlled by host rock texture and varied bulk chemistry, together with the nature of circulating fluids. Â© 2019